Effect of imperfect channel state information and co‐channel interferences on two‐hop fixed gain amplify‐and‐forward relay networks with beamforming. (16th June 2014) - Lin, Min; Wei, Heng; An, Kang; Ouyang, Jian; Huang, Yongming
Summary This letter investigates the joint effects of imperfect channel state information and co‐channel interferences on a two‐hop fixed gain amplify‐and‐forward (AF) relay network with beamforming. Specifically, the analytical expressions of the outage probability and the average symbol error rate for the AF relaying are derived. Moreover, the asymptotic analysis at high signal‐to‐noise ratio is also presented to reveal the diversity order and array gain of the considered AF relay system. Finally, computer simulations are given to confirm the validity of the analytical results. Copyright © 2014 John Wiley & Sons, Ltd.